2022
DOI: 10.1590/0074-02760220019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-therapeutic strategy targeting parasite and inflammation-related alterations to improve prognosis of chronic Chagas cardiomyopathy: a hypothesis-based approach*

Abstract: Chagas disease (CD), caused by infection by the protozoan parasite Trypanosoma cruzi, presents as main clinical manifestation the chronic chagasic cardiomyopathy (CCC). CCC afflicts millions of people, mostly in Latin America, and vaccine and effective therapy are still lacking. Comprehension of the host/parasite interplay in the chronic phase of T. cruzi infection may unveil targets for rational trait-based therapies to improve CCC prognosis. In the present viewpoint, I critically summarise a collection of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
9
0
2
Order By: Relevance
“…Network pharmacology along with the system biology paradigm have both provided a breakthrough in drug discovery research by establishing the relationship between drug molecules and disease, and the potential therapeutic targets [75]. The development of multi-target therapeutics drug compounds is likely to be a promising paradigm for discovering drugs and offer a greater efficacy level with minimal or no adverse effects and toxicity compared to monotheraputic drug compounds [76]. A study has reported herbal medicine to be characterized by multi-components/compounds and multi-targets with promising prospects for the discovery of new lead drug compounds with multi-therapeutic use [68].…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology along with the system biology paradigm have both provided a breakthrough in drug discovery research by establishing the relationship between drug molecules and disease, and the potential therapeutic targets [75]. The development of multi-target therapeutics drug compounds is likely to be a promising paradigm for discovering drugs and offer a greater efficacy level with minimal or no adverse effects and toxicity compared to monotheraputic drug compounds [76]. A study has reported herbal medicine to be characterized by multi-components/compounds and multi-targets with promising prospects for the discovery of new lead drug compounds with multi-therapeutic use [68].…”
Section: Discussionmentioning
confidence: 99%
“…There is a bulk of evidence that parasite persistence in tissues associated with ill-adapted homeostatic mechanisms, such as oxidative/anti-oxidative and pro-inflammatory/anti-inflammatory processes, are critical for the pathogenesis and progression of organ dysfunction in CD. 18 , 19 …”
mentioning
confidence: 99%
“… 19 In Chagas’ heart disease, low-level cardiac inflammation is linked to low-grade parasite persistence, tissue injury, progressive fibrosis, electrical abnormalities, and dysfunction, potentially evolving to heart failure. 18 , 19 The progression from IND to CARD form, and its severity (mild, moderate, severe), have been directly associated with the levels of the systemic inflammatory profile, revealed as increased serum levels of inflammatory (TNF, IL-6, IL-17, IFNγ, CCL2/MCP1) and regulatory/anti-inflammatory (IL-4, IL-10, TGFβ) cytokines, inflammatory mediators as nitric oxide, and reduced anti-oxidant enzymes as superoxide dismutase (SOD) and glutathione peroxidase (GPx), supporting inflammatory/anti-inflammatory and oxidant/anti-oxidant imbalance. 62 , 63 This is a quite relevant trait.…”
mentioning
confidence: 99%
See 2 more Smart Citations